Iatrogenic Injuries Related to Thermal Ablation of the Liver and Pancreas - HonShideler, Curtis; Lin, Liz; HonShideler, Kelsey; Guez, David; Bader, Mohammad (Digestive Disease Interventions, 2023)
Thermal ablation is a widely utilized treatment option for tumors of the liver and pancreas; procedures may be performed intraoperatively or percutaneously, under image guidance (more recently, endoscopy-guided ablation of pancreatic tumors has also been introduced). Through differing mechanisms, radiofrequency ablation, microwave ablation, and cryoablation aim to precisely eradicate tumor, with adequate margins and minimal injury to normal surrounding tissue. Knowledge of thermal ablative risks and complications is crucial for both therapeutic planning and postprocedural management to optimize outcomes and avoid significant patient injury. In this review, we discuss iatrogenic injuries related to thermal ablation of hepatic and pancreatic malignancies.
Keywords: complications; thermal; ablation; imaging